Performance optimization of CO2 heat pump water heater. (January 2018) - Nawaz, Kashif; Shen, Bo; Elatar, Ahmed; Baxter, Van; Abdelaziz, Omar
Highlights: An HPWH model has been developed and calibrated using previous experimental data. The impact of ambient temperature and water supply temperature has been reported. The performance of the sCO2 heat pump water heater has been compared to an R-134a-based system. The impact of wrap configuration vs. gas cooler configuration has been investigated. The impact of water circulation rate has been reported. Abstract: A preliminary analysis was conducted to analyze the performance of a heat pump water heater (HPWH) that uses CO2 as the refrigerant. A model to predict the performance was developed and calibrated based on the experimental data for an existing HPWH using a CO2 refrigerant. The calibrated model was then used to run a parametric analysis in which factors such as water supply temperature, water circulation rate, tank stratification, and condenser configuration were considered. The performance of a commercial CO2 system was compared with that of a similar system using R-134a as the refrigerant. It was found that CO2 HPWH performance was comparable to that of an R-134a HPWH, more so for a separated gas cooler configuration. For comparable performance, the compressor size and the tube-in-tube heat exchanger (condenser/gas cooler) size were compared for CO2 - and R-134a-based systems. The impact of the water circulation rate on the water temperature stratification in the tank, an essential requirement for higher performance for CO2 HPWH systems was also investigated.